Die biblische Vorstellungswelt und deren geschlechterpolitische Dimension – Methodologische Überlegungen am Beispiel der ersttestamentlichen Kategorien ‚rein‘ und ‚unrein‘ (lectio difficilior, 2003)
With a view towards methodology the author attempts to critically examine today’s feminist discussion about perceptions of pure and impure in the Hebrew Bible. In particular she directs her attention to the ongoing discussion by Christian feminists who look at the subject by taking issue with anti-judaism. On the other hand the author wishes to consider how we can find in general methodologies of analysing gender within the framework of the biblical world. Within the Christian feminist debate she criticizes the tendency of falling into at times even apologetical patterns of argumentation which are of no help in setting forth perspectives on how criticism of anti-judaism and feminist criticism can work together. Concerning the approach towards the ideology of gender, the author pleads for following up particular avenues of biblical discourse in a careful and sensitive way by continually keeping an eye on both positive and negative tendencies in ideologizing gender. [1]